(untitled) (k:ON - Kölner Online Journal für Lehrer*innenbildung, 2020)
Das Experiment ist zentraler Bestandteil des Chemieunterrichts und fordert Lehrer*innen in inklusiven Lerngruppen bei der Schaffung sicherer und förderlicher Voraussetzungen heraus. Der Beitrag stellt ein Projektseminar vor, in dem eine Möglichkeit aufgezeigt wird, wie angehende Chemielehrer*innen mit Hilfe von Classroom-Management-Strategien diesen Herausforderungen begegnen können und das Gemeinsame Experimentieren von Schüler*innen praxisnah (an-)leiten. Experiments are an integral part of teaching chemistry. Nonetheless, they pose a challenge for teachers in inclusive learning environments when it comes to creating and ensuring safe and supportive learning conditions. This article describes a project seminar aiming at fostering classroom management expertise of future chemistry teachers during university education. The pre-service chemistry teachers get the possibility to develop the necessary classroom management expertise. Consequently, they acquire skills to meet these challenges and to put Cooperative Experimenting into practice.